The presence of black women in higher education and as teachers in higher education - Ângela Siqueira, Andressa; Maria Teixeira Amorim, Mônica (Educação, Escola & Sociedade, 2022)
This article proposes to address recent statistics and research alluding to the presence of black students in Brazilian higher education (undergraduate and graduate) and the trajectory of black women who graduated from stricto sensu graduate courses, with attention to those who work as teachers in higher education. It is the result of an investigation that involved a bibliographical study, analysis of secondary data and the application of questionnaires to graduates of the Graduate Program in Social Development (PPGDS) at UNIMONTES. The results indicate an increase in the presence of women in Brazilian undergraduate and graduate programs, including an increase in the number of black women in these educational spaces. Furthermore, it reveals that there is a significant percentage of black graduates from the PPGDS, higher than white, who work in higher education teaching.